METODE UNWEIGHTED MEANS UNTUK FAKTORIAL TAK SEIMBANG DISPROPORSIONAL - WURYANDARI, TRIASTUTI (MATEMATIKA, 2007)
A factorial design should be used when there are several factors of interest in experiment. The problem which arises when the factorial experiment does not contain equal sized samples in the cells is that the design is nonorthogonal. In other words, the total sums of squares in the ANOVA table cannot be decomposed into a series of additive components which permit the analysis of the separate effect. There are possible situations when the cell sample sized are unequal, allocated proportionately or disproportionately. On the allocated disproportionately, approximate F test using the method of unweighted means. Â